Herpetofauna Trade Via Online Media - Rahmadhiani Nurdin; Maria Purnama; Fadlan Pramatana; Yusratul Aini (Jurusan Kehutanan -FHIL-UHO, 2025)
The increasing use of internet media in Indonesia, as well as the trend of trading that has shifted from conventional methods to online media, allows for an increase in herpetofauna trading activities. This study aims to determine the online trading media of herpetofauna and herpetofauna trading areas online. The research method used was a direct search through online media. The results found that the Tokopedia platform was recorded as the online media with the most accounts (60%) offering herpetofauna products both in the form of live animals and processed animals, followed by Shopee (23%), and Facebook (17%), and found that West Java and Jakarta provinces as the most herpetofauna trading areas.